The importance of compensation for maintaining employees performance: case study at Jaya Jusco, Ayer Keroh, Malacca - Kamaruddin, Azlina (2004)
The research study has been successfully being done by the researcher at Jaya Jusco, Ayer Keroh, Malacca. The researcher had choose this organization as the location for study of the topic of compensation in maintaining the employees performance. In the first chapter, it will explain about the issue arises where it includes the problem statement. Besides, it needed to identify the objective of this research. Researcher also need to know the scope of the research before it is been done. In this chapter also, it will explain the significance of this study, several limitation that are faces by the researcher. It also includes the several key terms and concepts based on the research topic. In the second chapter, it is more on the literature review that need to identify on the different conceptual from the different people who have such opinion on the topic being studied. In the third chapter will explain about the methods that been used by the researcher. Other than that, it will explain the sample size on how many of the total population that being studied, the sampling technique used, data collection and data analysis. In the fourth chapter it will explain about the findings of the research. It is included the profile of the respondents in order to fill the SPSS program. The researcher can get information from the data that been gain from the respondents. In the last chapter, includes the conclusion and recommendations that been made by the researcher.